2020
DOI: 10.3390/geosciences10080314
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Wetlands Stratigraphy: Geophysics and Soil Parameters for Investigating Ancient Basin Development at Lake Duvensee

Abstract: We present a case study of a bog showing how an integrated approach of multi-method geophysical sounding and local soil sampling can be used to identify, differentiate, and map organic sediments. Our study is based on ground-penetrating radar (GPR), electrical resistivity tomography (ERT) and shear-wave seismic (SH seismic) profiling applied to sediments of the former Lake Duvensee (northern Germany), nowadays a bog. This is a well-known locality for remains from the Mesolithic hunter-gatherers’ occupation tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Several coring and geophysical campaigns have been performed to clarify and confirm the location and extent of the former islands hosting Mesolithic camps. The work of [10] and [17] present the results of a large-scale 200 MHz GPR investigation that confirmed the location of five former islands hosting Mesolithic camps and improved the knowledge of their size and shape (Figure 1b). Moreover, this survey allowed a 3D reconstruction of the basin's evolution between the early Boreal and the Subboreal bio-zones.…”
Section: Geo-archaeological Background and Previous Workmentioning
confidence: 69%
See 1 more Smart Citation
“…Several coring and geophysical campaigns have been performed to clarify and confirm the location and extent of the former islands hosting Mesolithic camps. The work of [10] and [17] present the results of a large-scale 200 MHz GPR investigation that confirmed the location of five former islands hosting Mesolithic camps and improved the knowledge of their size and shape (Figure 1b). Moreover, this survey allowed a 3D reconstruction of the basin's evolution between the early Boreal and the Subboreal bio-zones.…”
Section: Geo-archaeological Background and Previous Workmentioning
confidence: 69%
“…The gradual infilling of the basin was accompanied by a general decrease in the water level over time and land amelioration, such that by the 19th century CE, most of the basin was occupied by a bog. The authors of [10,17] suggested a model that reconstructs the lake infilling using the stratigraphy and morphology inferred from the geophysical results. Today, a total of 23 Mesolithic camps, named Wohnplatz (WP), have been found at Duvensee, of which 17 have been partly excavated.…”
Section: Geo-archaeological Background and Previous Workmentioning
confidence: 99%
“…Additionally, direct push electrical conductivity sensing resulted in a highly depth-accurate dataset that noticeably improved the spatial significance of common, non-invasive ERT applications e.g., [22,37,81]. Thus, there is a high methodologi-cal potential for future combinations of depth-accurate direct push electrical conductivity logging as point-by-point ground-truthing with ERT data sets [17,24,82,83].…”
Section: A Multi-methods Approach With High-resolution Direct Push Sensingmentioning
confidence: 99%
“…Poor peatland management can lead to degraded land, forest, and land fires. Land-use conversion of about 10 million ha of peatland results in annual emissions of 132-159 Mt C year -1 from peat oxidation and will increase greenhouse gas emissions [45]. Agroforestry is one alternative that can be proposed for peat restoration activities.…”
Section: The Role Of Agroforestry As a Rainwater Regulator (Soil And ...mentioning
confidence: 99%